2021
DOI: 10.3390/molecules26154484
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Drying Techniques Regulate Secondary Metabolites and Anti-Neuroinflammatory Activities of Ganoderma lucidum

Abstract: Ganoderma lucidum extract is a potent traditional remedy for curing various ailments. Drying is the most important postharvest step during the processing of Ganoderma lucidum. The drying process mainly involves heat (36 h at 60 °C) and freeze-drying (36 h at −80 °C). We investigated the effects of different postharvest drying protocols on the metabolites profiling of Ganoderma lucidum using GC-MS, followed by an investigation of the anti-neuroinflammatory potential in LPS-treated BV2 microglial cells. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The heat-dried extract was differentiated due to a high level of amino acids (L-Alanine, L-Serine, L-Asparagine, L-Proline, and L-Threonine); alcohols and derivatives (D Mannitol, glycerol, ethylene glycol and silanol) and monosaccharides (D-(−)-fructose, D-(+)-mannose and D-(−)-ribofuranose). In the freeze-dried samples, the organic acids were found to be significantly higher [17].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The heat-dried extract was differentiated due to a high level of amino acids (L-Alanine, L-Serine, L-Asparagine, L-Proline, and L-Threonine); alcohols and derivatives (D Mannitol, glycerol, ethylene glycol and silanol) and monosaccharides (D-(−)-fructose, D-(+)-mannose and D-(−)-ribofuranose). In the freeze-dried samples, the organic acids were found to be significantly higher [17].…”
mentioning
confidence: 90%
“…G. lucidum has been used in herbal medicine for many years to treat human diseases, including cancer, viral hepatitis, and bronchitis, and more. Previous studies worldwide have reported that the G. lucidum extract could elicit innate immune responses, control cell proliferation, and cause cancer cell migration [17].…”
mentioning
confidence: 99%
“…Some substances of traditional Marsdenia tenacissima may also promote the growth and metabolism of medicinal Ganoderma lucidum and the production of active ingredients. Ganoderma lucidum may also change its metabolic pathways in the particular environment of Marsdenia tenacissima with Ganoderma lucidum and compound prescriptions, thus forming new active ingredients or changing the relationship between active ingredients ( Sadiq et al, 2021 ). This study focused on the biotransformation of Marsdenia tenacissima with the help of Ganoderma lucidum enzyme system, with the aim of co-fermenting Marsdenia tenacissima with Ganoderma lucidum in culture.…”
Section: Introductionmentioning
confidence: 99%